Didactics and teaching practices based on competencies: Critical Educational Model with a Competency Approach (volume 2) (2021)
This book shows the experiences and results of classroom exercises based on the postulates of the critical educational model with a focus on competencies (MECCEC). The researches that make up this volume address fundamental problems for teaching and learning processes from didactics. In the first instance, the chapter "Knowledge, attitudes, and teaching practices for the competency model in a Colombian multicampus university" seeks to answer the question: how do our teachers teach? The research focuses on understanding how UCC teachers have assumed the competency model. From there, the evidence is extracted to identify didactic strategies that enhance classroom practices, as well as potentialities that can be developed and opportunities for improvement. In the second chapter, "From critical didactics to teaching strategies for the development of skills in critical reading and written communication", an analysis is made of what are the contributions of critical didactics to teaching strategies for the development of said competences in the Public Accounting program. The final chapter, "Didactic strategies to develop a process of accounting education with a focus on competencies at the Cooperative University of Colombia", responds, through an on-site analysis exercise, to how the implementation of the educational model has transformed the curriculum since the perspective of the general didactics and proposes strategies that facilitate the monitoring and evaluation of the model, with actions that allow improving the relationship between teachers and students in the classroom.